Reimagining Human–Nature Interactions Through the Lens of “Green Education Principles” - Dimitri Jan Jakubowski (Philosophies, 2025)
The research explores three interconnected themes: philosophy, education, and ecology. It aims to be an interdisciplinary study that emphasizes the significance of the philosophy of environmental education and its practical implications. Initially, it addresses the contemporary hylomorphic production approach, followed by proposing educational solutions aimed at fostering a comprehensive understanding of the environment. This understanding includes recognizing humans as part of the environment, sharing equal rights to existence with all other life forms. The study advocates for a shift away from anthropocentrism, positioning humans in a non-privileged role within the ecosystem. It seeks to challenge long-standing notions where humans have historically placed themselves above other beings. The research is particularly inspired by the “Green Schools” in Bali, which embody a proactive educational philosophy aimed at reshaping how future generations perceive their role in production and environmental stewardship. These schools promote an educational framework that encourages students to reconnect with nature and develop sustainable practices from the ground up, moving away from exploitative and profit-driven paradigms. An example of this innovative approach is found in disciplines such as “eco-art,” where colors are derived from natural relationships rather than manufactured. The overarching goal is to cultivate a perspective that sees humans as integral components of nature, valuing it for its intrinsic worth rather than solely for its utility to humanity.